Pengaruh Kualitas Hubungan, Faktor Pendorong dan Faktor Penarik Motivasi terhadap Kepuasan dan Loyalitas Orang Tua Siswa di Sekolah XYZ Bogor: Pengaruh Kualitas Hubungan, Faktor Pendorong dan Faktor Penarik Motivasi terhadap Kepuasan dan Loyalitas Orang Tua Siswa di Sekolah XYZ Bogor - Herijanto (Jurnal Ketopong Pendidikan, 2023)
The competition among private schools is currently becoming increasingly competitive and attractive from year to year. The number of students in a school serves as one of the indicators reflecting the development and sustainability of that school. As competition intensifies, many educational institutions need to understand the importance of creating and building parental loyalty as a competitive strategy that provides long-term advantages. Parental loyalty can benefit schools by ensuring that parents continue to entrust their children’s education to the same institution and by providing referrals for new students. This study aims to further investigate and evaluate the influence of relationship quality, push factors, and pull motivation factors on the satisfaction and loyalty of parents while entrusting their children’s education to sekolah XYZ Bogor School. The sample in this study was determined using a census method, involving 88 parent/guardian respondents of seventh- to tenth-grade students who had been enrolled for at least one year at sekolah XYZ Bogor School. The results indicate that the variables of relationship quality, push factors, and pull motivation factors affect parental satisfaction and loyalty. This is shown by the coefficient of determination (R²) results, where parental satisfaction is explained by 0.551 or 55.1%, while parental loyalty is explained by 0.754 or 75.4%, with the remaining 24.6% influenced by other variables outside the scope of this study.